Application of different CO2 pneumoperitoneum pressure in laparoscopic pyeloplasty for infants with ureteropelvic junction obstruction - Peng, Yan; Zhu, Min; Chen, Chunmei (Frontiers in Pediatrics, 2024)
Background: Laparoscopic pyeloplasty is a minimally invasive approach for the therapy of infant ureteropelvic junction obstruction (UPJO), reliant on CO2 pneumoperitoneum insufflation. While the impact of CO2 insufflation on adult and older pediatric populations has been studied, its effects on infants remain less explored.Methods: This prospective randomized controlled trial included infants with UPJO undergoing laparoscopic pyeloplasty. Patients were allocated to low pneumoperitoneum pressure (LPP, 5 mmHg) or high pneumoperitoneum pressure (HPP, 8 mmHg) groups. Surgical parameters, postoperative complications, acid-base balance, stress markers, inflammatory cytokines, and oxidative stress markers were evaluated and compared.Results: A total of 116 infants were analyzed. Preoperative characteristics were comparable between LPP and HPP groups. No significant differences in blood loss, operation time, or hospitalization time were observed. Postoperative complications were similar between groups. Acid-base balance analysis revealed a decrease in pH after pneumoperitoneum in both groups, with greater reductions in actual base excess and standard base excess in the HPP group. Stress markers, cytokines, and oxidative stress markers increased postoperatively in both groups, with higher levels in the HPP group.HPP leads to more pronounced physiological responses, including acidbase alterations, stress reactions, and inflammatory cytokine elevations.